TINJAUAN TERHADAP PENERAPAN SURCHARGE OLEH PELAKU USAHA KEPADA KONSUMEN DALAM TRANSAKSI MENGGUNAKANKARTU KREDIT - Lubis, Putri Mirta Fitriyanti; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The implementation of credit card is inseparable from the legal relationshipthat occurs behind it all, the legal relationship between the credit card companyand the credit card holder or the merchant, as well as the legal relationshipbetween the credit card holder and the merchant where the credit card holder isshopping. In the regulations there is no regulation clearly related to surchargeeven in the explanation.This type of research can be classified in the type of sociological legalresearch, because in this study the authors immediately conduct research on thelocation or place under study in order to provide a complete and clear picture ofthe problem under study. This research was conducted in Pekanbaru City, whilethe population and samples were Cards and Merchant Business Managers,Assistant Sales Cards and Merchant Business, Merchant Branch Relationship,Merchants, and Consumers. The data sources used are primary data, andsecondary data. Data collection techniques in this study were interviews,questionnaires, and literature review.The conclusion that can be obtained from the results of the study is Theapplication of Surcharge by Business Actors to Consumers is very detrimentaland does not provide a sense of justice for consumers. business actors who stillmake additional costs to consumers without considering the objections ofconsumers in each transaction. Though the actions taken give a loss to consumersin each transaction. Protection of Consumers in the Application of Surcharge byBusiness Actors in Transactions using Credit Cards still does not fully obtainlegal protection, moreover consumers do not complain about the imposition ofsurcharge. efforts made by consumers towards the application of Surcharge inproviding Justice for Consumers by conducting a BNI Credit Card ComplaintsUnit via email or fax no later than seven days after the transaction date.Complaints from the card holder will then be examined and processed by the BNICard Business Unit no later than 14 working days and the additional fees chargedby the merchant will be returned in the form of a credit balance on the credit cardbill the following month.Keywords: Application, Surcharge, Merchant, Consumers, Transactions, CreditCards